Proceedings of the 5th International Congress on Sport Sciences Research and Technology Support 2017
DOI: 10.5220/0006505500480055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selection of Release Angle and Speed on Success Rates of Jump Shots in Basketball

Abstract: Enhancing the successful jump-shot percentages in basketball is critical for winning a game. A selection of release parameters and variability can influence the success rate, but the actual selection of the release parameters and variabilities in those during jump shots and the influence of this selection on success rate have not been investigated and are not understood well. Thus, the purpose of this study was to investigate the influences of the selection of release angle, release speed and spin rate, and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Similarly, in a recently published study, forearm positioning was found to be a key kinematic variable capable of distinguishing between proficient and non-proficient free-throw shooters [ 6 ]. To couple with previously mentioned findings Inaba et al [ 7 ] found that players with superior mid-range jump-shot performance had greater release height, lower release velocity, and a larger margin of error for the release speed. The authors also suggested that an increase in backspin rate may help with maintaining optimal release parameters such as speed and angle of the release, especially at lower release heights [ 7 ].…”
Section: Introductionmentioning
confidence: 70%
“…Similarly, in a recently published study, forearm positioning was found to be a key kinematic variable capable of distinguishing between proficient and non-proficient free-throw shooters [ 6 ]. To couple with previously mentioned findings Inaba et al [ 7 ] found that players with superior mid-range jump-shot performance had greater release height, lower release velocity, and a larger margin of error for the release speed. The authors also suggested that an increase in backspin rate may help with maintaining optimal release parameters such as speed and angle of the release, especially at lower release heights [ 7 ].…”
Section: Introductionmentioning
confidence: 70%
“…successful shot without contacting with hoop) based on (Brancazio, 1981), and green surrounding area represents a set of variables which result in a hoop shot ( i.e. possibly successful shot by contacting with hoop) as defined by the landing at ±5 cm relative to the swish shot as in the study of Inaba et al (2017). (d) The result error Δ Y caused by the execution error Δ θ , Δ v from a zero-error startegy.…”
Section: Methodsmentioning
confidence: 99%
“…release speed, angle, spin, and position) were defined from the center of ball at the time of release. The details of the calculation for experiment 1 and 2 are described in the studies of Nakano et al (2018) and Inaba et al (2017), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ref. [44], we also present the relationship between α 1 and v 1 for all competitors and for individual body height groups as shown in Figure 8. The blue dotted lines present the typical values for the analysed groups.…”
Section: Using In Practicementioning
confidence: 99%